2017
DOI: 10.1002/1873-3468.12783
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for the effect of the L31F mutation on CARD function in ARC

Abstract: The apoptosis repressor with caspase-recruiting domain (ARC) is aberrantly overexpressed in various cancers. ARC contains a caspase recruitment domain (CARD) that is the main mediator of protein-protein interactions. Mutation of Leu31 within the CARD of ARC to Phe (ARC_L31F) is widely used as a functionally defective mutant of ARC despite a lack of clear experimental evidence regarding how its functionality is lost. In this study, we show that L31 in helix 2 (H2) is critical for stabilization of the helix bund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…F164 is located in the helix bundle and forms a hydrophobic cluster with neighboring hydrophobic residues (L127, V135, and L180), which could be critical for maintaining the stability of six-helix bundle fold of the DD ( Fig 1D ). A previous study showed that CARD, another member of the DDS, is critical for interactions in the hydrophobic cluster, which in turn maintains the stability of the fold [ 38 ]. R170 is located in the type I interface, which is formed via interactions among the H4 of the first DD and H5-H6 loop and the H6 helix of the second DD ( Fig 1D ).…”
Section: Resultsmentioning
confidence: 99%
“…F164 is located in the helix bundle and forms a hydrophobic cluster with neighboring hydrophobic residues (L127, V135, and L180), which could be critical for maintaining the stability of six-helix bundle fold of the DD ( Fig 1D ). A previous study showed that CARD, another member of the DDS, is critical for interactions in the hydrophobic cluster, which in turn maintains the stability of the fold [ 38 ]. R170 is located in the type I interface, which is formed via interactions among the H4 of the first DD and H5-H6 loop and the H6 helix of the second DD ( Fig 1D ).…”
Section: Resultsmentioning
confidence: 99%
“…The ARC CARD contains a 5-helix bundle fold (H1-H5) instead of a 6-helix bundle (Fig. 1C and D) (42,61), with helix H6 being disordered and not present in the structure. This indicates that H6 in the CARD is not necessary for its function, and even for the function of the DD super-family (Fig.…”
Section: Structure Of Cardsmentioning
confidence: 99%
“…Several apoptosis inhibitors, including apoptosis repressor with CARD (ARC), also contain CARDs (40,41). ARC may inhibit death-inducing signaling complex assembly followed by caspase activation by binding to the Fas-associated protein with DD (FADD) DD, Fas DD and caspase-8 DED using its CARD (42-44). This protein also inhibits p53 tetramerization and the function of p53 (45).…”
Section: Introductionmentioning
confidence: 99%
“…ARC antagonizes the intrinsic pathway by interacting with apoptosis-associated proteins (11). The binding of ARC and Bax, which can inhibit Bax activation and accumulation in the mitochondria (15), increases the Bcl2 apoptosis regulator/Bax ratio (71,72), stabilizes the mitochondrial membrane and prevents cytochrome c release (27,73,74). Furthermore, ARC is also involved in the regulation of mitochondrial dynamics.…”
Section: Cytoprotection and Anti-apoptosis Mechanisms Of Arcmentioning
confidence: 99%